PREVENTION OF FOREIGNERS ENTRY INTO INDONESIAN TERRITORIAL AREA ILLEGALLY - Aim, Heru Al Zulkifli; Haryono, Waty Suwarty; Patramijaya, Arief (JILPR Journal Indonesia Law and Policy Review, 2025)
The objectives to be achieved in this study are to determine the causes and efforts to prevent foreigners from entering the Indonesian territorial area illegally. The research method used in this study is normative juridical (normative legal research method). Efforts that can be made to overcome the illegal entry and exit of foreigners include: First, cooperation with immigration in improving the performance of immigration intelligence. Second, create an online foreign national reporting system. Currently, the Directorate General of Immigration has created an online foreign national reporting system or https://apoa.imigration.go.id/. Third, provide a maximum criminal penalty where if reviewed from the regulatory arrangements above, namely for a maximum of one year, this penalty is considered too light even though the state losses incurred are quite large. This is the reason that many foreigners go through back channels to enter Indonesia.